Un enfoque de estadística espacial para explorar la geodemografía de los ninis en la Zona Metropolitana de la Ciudad de México - Navarrete, Emma Liliana; Trujillo, Armando; Garrocho, Carlos; Cadena, Edel (El Colegio de México A.C., 2020)
We examine the geodemography of NEET (not in education, employment or training) inside the Metropolitan Area of Mexico Citywith spatial statistics. As far as we know, the literature on NEET do not report studies with our statistical approach. We explore four key questions: How many are they? Where are they? How is explained their spatial distribution? Does accessibility to employment and education opportunities affect the presence of NEET? Given the seminal nature of our approach, we address the questions with a socio-spatial vision, without making, for now, deep cuts of variables such as sex, schooling and othercharacteristics of the home of NEET. The results open new research paths.